(untitled) (Research, Society and Development, 2024)
The present study analyzes the effects of regular physical exercise on elderly people diagnosed with depression, a topic that has aroused increasing interest among professionals from different areas due to the significant increase in the prevalence of depressive disorder in this population and the consequent need for effective strategies to deal with the problem. The objective of this study is to describe the impacts and benefits that physical exercise brings as a means of intervention in the treatment of depression in elderly individuals. The research, with a qualitative, descriptive and bibliographical approach, was conducted through the analysis of articles available in relevant databases and other research tools, using the descriptors "depression", "elderly", "mental health" and "physical exercise ". The results indicated that physical exercise has positive effects on both the prevention and treatment of depression, and all the articles analyzed corroborate this conclusion. Furthermore, it was found that physical activity also contributes to the prevention and treatment of other health conditions not directly addressed in this study, such as cancer, anxiety, cardiovascular diseases and memory improvement, among others.